Historical bases of Chinese-Kazakh language relations - Mustafauly, S. (Journal of Oriental Studies, 2023)
The article analyzes the historical linguistic relations between the Chinese and Kazakh languages, which have developed in the mists of time. In the field of linguistic research, modern linguistics proves that the study of the language of each nation in combination with its past history, their social environment, interaction with other peoples is the best way to obtain the necessary information from the history of the development of languages. Studying the vocabulary of the Kazakh literary language on the basis of ancient Kazakh words, comparing them with the historically neighboring Chinese language, provides an excellent opportunity to study the past history of the Turkic languages, as well as determine the historical basis of the Dictionary of the Kazakh language. It is known that the relationship of languages ​​depends on mutual hostility, political, economic and cultural relations of neighboring peoples at different stages of historical development. It is well known that words are a linguistic unit that tends to move from one language to another, and from there to a third, and it is natural that Turkic words penetrate into the ancient Chinese language. The article reveals the possibility of gaining the meaning of many words in our language, the disclosure of their unclear meaning, the relationship of the Kazakh people with other peoples in different eras, or the possibility of obtaining detailed information about their past.